2017
DOI: 10.1093/cid/cix214
|View full text |Cite|
|
Sign up to set email alerts
|

Sofosbuvir-Daclatasvir-Simeprevir Plus Ribavirin in Direct-Acting Antiviral–Experienced Patients With Hepatitis C

Abstract: We assessed the broadly used, off-label combination of sofosbuvir, daclatasvir, simeprevir, and ribavirin in direct-acting antiviral-experienced patients, as recommended in current guidelines despite scarce data. After 24 weeks' treatment, sustained virological response 12 weeks after the end of treatment was achieved in 6 patients (60%). Two cirrhotic patients relapsed and 2 discontinued treatment due to serious adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The authors hypothesized that, contrary to EASL guidelines, 12 weeks of treatment with sofosbuvir/ledipasvir might not be optimal in treatment‐experienced patients. In another small real‐world study based on EASL guidelines, the combination of sofosbuvir, daclatasvir, simeprevir, and ribavirin for 24 weeks was examined in 10 treatment‐experienced patients . SVR12 was obtained in 60% (n = 6/10) of patients (2 patients with cirrhosis relapsed and 2 discontinued treatment due to serious adverse events).…”
Section: Efficacy In the Real‐world Settingsupporting
confidence: 71%
See 3 more Smart Citations
“…The authors hypothesized that, contrary to EASL guidelines, 12 weeks of treatment with sofosbuvir/ledipasvir might not be optimal in treatment‐experienced patients. In another small real‐world study based on EASL guidelines, the combination of sofosbuvir, daclatasvir, simeprevir, and ribavirin for 24 weeks was examined in 10 treatment‐experienced patients . SVR12 was obtained in 60% (n = 6/10) of patients (2 patients with cirrhosis relapsed and 2 discontinued treatment due to serious adverse events).…”
Section: Efficacy In the Real‐world Settingsupporting
confidence: 71%
“…Real‐life studies have also either shown newly diagnosed or identified worsening of pulmonary arterial hypertension in patients treated with sofosbuvir‐containing combinations . This has usually been observed in patients who already had concomitant risks factors for pulmonary arterial hypertension.…”
Section: Safety Considerationsmentioning
confidence: 87%
See 2 more Smart Citations
“…(4,5) Therefore, effective retreatment of patients who have had VF on NS5A inhibitor-containing regimens has been challenging, and retreatment options for this population are currently limited. (6,7) Addition of ribavirin (RBV) and/or extended treatment durations using combinations of three to four DAAs have been strategies utilized to provide retreatment options for patients (2,(8)(9)(10)(11)(12) ; however, clinical data from large studies are not available for most of these regimens, and sustained virological response (SVR) rates have generally been suboptimal. Recently, the three DAA fixed-dose combination of sofosbuvir (SOF)/velpatasvir (VEL)/voxilaprevir demonstrated an overall 96% SVR12 rate in patients with past NS5A inhibitor experience.…”
mentioning
confidence: 99%